Morphophysiological Responses of Pakchoi in Variations of Watering and Growing Media in Vertical Fertigation System - Wilda Lumban Tobing; Azor Yulianus Tefa; Natalia Desy Djata Ndua (Agro Bali : Agricultural Journal, 2026)
Pakchoi productivity in dryland areas is often constrained by water availability and suboptimal nutrient management strategies. However, the combined role of organic growing media, boron supply, and controlled irrigation in a vertical-wick fertigation system under dryland conditions remains underexplored. This study aimed to assess the presence of boron in compost- and biochar-modified growing media under water stress, which affects the morphophysiology of pakchoi in dryland conditions, using a vertical system with wick fertigation. The study was arranged in a split-plot design with two watering frequencies and a growing media formulation based on soil, compost, and biochar, with added boron. The results showed that watering frequency and boron-based growing media significantly affected leaf number, shoot and root biomass, root characteristics, and chlorophyll content. Consistent daily watering resulted in better growth and yield compared to watering every other day. Optimized combinations of regular irrigations and appropriate boron application enhanced biomass accumulation and chlorophyll content, indicating improved plant performance. These findings indicate that regular water management through a wick fertigation system, combined with organic growing media formulation and appropriate boron dosage, can significantly enhance pakchoi growth and productivity in dryland conditions. Importantly, this study provides a practical and scalable strategy for improving vegetable production under water-limited conditions.